Decentralisation in the health sector and responsibilities across levels of government Impact on spending decisions and the budget - James, Chris (OECD Publishing, 2019)
This article sheds light on the role of subnational governments in health systems across OECD countries. The views in this article show a move away from traditional measures of decentralisation, such as the share of subnational government expenditure of total expenditure, to measures capturing a range of responsibilities in the health sector. The data comes from the 2017 OECD Survey on Performance Measurement Systems in the Health Sector and Responsibilities across Levels of Government. The results show that despite health representing a large sector of subnational government expenditure, central governments still have considerable decision-making power. This power applies to key policy-making and budgeting decisions
Keywords: Finance and Investment; Governance; Social Issues/Migration/Health; Economics